Australian Female Board Representation - Song , Xiaoyang (Journal of Law and Governance, 2015)
This article provides a descriptive analysis of the increase in female directors on Australian company boards from 2001 to 2010. After outlining the female board representation of the largest 500 companies in Australia based on their ASX market capitalisation from 2001 to 2010, an overall snapshot of the female participation on boards is based on a general, industry, corporate and individual level. With an increasing representation since 2001 to 2010, female directors consistently have more seats in the boardrooms of Insurance and Banking companies; while in Energy, Materials and Utilities sectors, female directors have been under-represented. In addition, female directors are most likely to serve on Audit Committee and are more likely to chair Audit Committee and Remuneration Committee. The findings of this article examine the effectiveness of existing gender diversity initiatives and shed a light on future corporate governance proposals advocating greater gender diversity on company boards.